ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PELATIHAN DAN PENGEMBANGAN, SERTA MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BPR BKK JATENG (PESERODA) CABANG KARANGANYAR - Erlina Sih Rahayu; Erni Widiastuti (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the influence of transformational leadership, training and development, and work motivation on the performance of PT employees. BPR BKK Central Java (Peseroda) Karanganyar Branch. The hypotheses in the research include: (1) transformational leadership has a significant effect on the performance of PT employees. BPR BKK Jateng (Peseroda) Karanganyar Branch, (2) Training and development have a significant effect on the performance of PT employees. BPR BKK Jateng (Peseroda) Karanganyar Branch, and (3) Work motivation has a significant effect on the performance of PT employees. BPR BKK Central Java (Peseroda) Karanganyar Branch. The research method used is a quantitative research method using primary data and secondary data. The sample in this study was 48 respondents. The sampling technique uses random sampling. The data collection method used in this research was by distributing questionnaires to respondents taken as samples. Data analysis used in this research was statistical tests including instrument tests, multiple linear regression tests, t tests, F tests, and coefficient of determination tests. The results of the t test and F test show that transformational leadership, training and development, and work motivation have a significant effect on the performance of PT employees. BPR BKK Central Java (Peseroda) Karanganyar Branch. The results of the coefficient of determination test show that transformational leadership (X1), training and development (X2), and work motivation (X3) have contributed to the performance of PT employees. BPR BKK JATENG (Peseroda) Karanganyar Branch was 87.9% while the remaining 12.1% was influenced by other factors such as organizational culture, work-life balance, reward and recognition system, working conditions and facilities, etc. Keywords: Transformational Leadership, Training and Development, Work Motivation and Employee Performance